Analysis Of Production Performance In The Legend Luwak Coffee Business, Kepahiang - Herri Fariadi Lubis; Indah Fitria (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Coffee is a type of plantation crop that has long been cultivated and has high economic value. This study aims to determine the production performance of the legendary civet business in Kepahiang Regency. The research method used in this research is productivity analysis, capacity, quality, and delivery speed. While the production performance is seen from Productivity, Capacity, Quality, and Speed ​​of Delivery. The results showed that the labor productivity of the legendary civet coffee business was 15.24 with a good category, the resulting capacity was 0.67 kg in a good category, the quality of robusta coffee powder products was 35.46 in a good category, fast product delivery. Robusta coffee powder in the business of legend luwak with an average of 35.56 in the fast category.